KNOWLEDGE, ATTITUDE AND PRACTICES ON ANTIBIOTIC USE AND RESISTANCE AMONG DOCTORS IN B.P. KOIRALA INSTITUTE OF HEALTH SCIENCES - Sarraf, Deependra Prasad; Rai, Dillisher; Rauniar, Gajendra Prasad (Journal of Drug Delivery and Therapeutics, 2018)
Background: Assessment of knowledge, attitudes and practices (KAP) of antibiotic prescription among doctors may help in developing guidelines to improve antibiotics use and decrease resistance. Aims and objectives: Our aim was to evaluate KAP regarding antibiotic use and its resistance among doctors. Materials and Methods: A cross sectional, questionnaire based study was conducted among the doctors of B.P. Koirala Institute of Health Sciences, Dharan, Nepal between January-March 2016 and their KAP regarding antibiotic use and resistance was assessed by using a five point Likert scale. The data were analyzed by calculating percentage and frequency. Results: Almost half of the doctors (50.2%) used to prescribe antibiotics more than once daily. Nearly two thirds of the doctors (65.3%) received antibiotic education at a formal lecture on ward rounds. Most of the doctors (87.4%) agreed that antimicrobials are overused. One hundred thirty four doctors (42.3%) agreed that patients’ demands for antibiotics contribute to its overuse. Nearly two third doctors (70.7%) believed that locally developed antimicrobial guidelines would be more useful. Most of the respondents (89.9%) wanted more ongoing education on antibiotic use and its resistance. Conclusions: Our study reveals that antibiotics are overused and patients’ demand contribute to this. Locally developed antimicrobial guidelines would be more useful. More CME on antibiotic use and its resistance should be conducted to enhance the awareness among doctors. Keywords: Antibiotics; Attitude; Antimicrobial drug resistance; Knowledge.